Atraumatic restorative treatment in atypical cavities - Letícia Simino Carvalho; Janaina Merli Aldrigui; Clarissa Calil Bonifácio; José Carlos Pettorossi Imparato; Daniela Prócida Raggio (Faculdade São Leopoldo Mandic, 2009)
The atraumatic restorative treatment has been widely divulged among professionals in the area of Pediatric Dentistry. This restorative technique is included in the philosophy of Minimal Intervention and is considered one of the most conservative treatments, because only the layer of infected dentin caries is removed. Moreover, the atraumatic restorative treatment has been shown to be less painful than conventional approaches, and local anesthesia is rarely required. After the removal of the infected dentin, the cavities are filled with glass ionomer cement, a material that has antimicrobial capacity, good marginal sealing and constant fluorine release and recharge. In spite of the increasing number of studies about atraumatic restorative treatment, only studies related to restorations in occlusal cavities have shown scientific evidences about the technique. The aim of this study was to evaluate the feasibility of atraumatic restorative treatment in cavities with 3 or more surfaces involved, by means of a clinical case report of a patient with extensive dstruction in primary teeth, who was submitted to atraumatic restorative treatment, and observe the result of the treatment after one year of clinical and radiographic control.